Characteristics of sars-cov-2 infection in healthcare workers at a maternal perinatal institute in Peru - admin, Investigación Materno Perinatal (2024)
Objective. To describe the characteristics of the infection by SARS-CoV-2 in health workers of a Instituto NacionalMaterno Perinatal in Peru. Methods. Observational, cross-sectional, descriptive study. In April 2020 and December2022 at Instituto Nacional Materno Perinatal. Al workers with COVID-19 infection identified by confirmatory test forSARS-CoV-2 were included. Results. 2250 confirmed cases of COVID-19 were detected. 76% were women, 71.3%were 30-59 years old, and 77.8% were health personnel. 47.8% were diagnosed by antigenic test, while 44.4% werediagnosed by molecular test. 18.7% had some comorbidity, 2.2% were hospitalized, and eight workers died. Conclusion. The findings show that healthcare workers have also been affected by the COVID-19 pandemic. The analysis ifthe behavior of the infection is relevant to continue developing and improving strategies for the prevention and controlof cases among workers.